Design optimization of multistable variable-stiffness laminates. Issue 1 (2nd January 2019) - Anilkumar, P. M.; Haldar, Ayan; Jansen, Eelco; Rao, B. N.; Rolfes, Raimund
Abstract: Exploiting the anisotropic nature of composite laminates is a driving factor to improve the design regime of multistable structures. The concept of laminate tailoring is being taken a step ahead by allowing variation in fiber angle orientation within the ply planform. Such composite laminates known as variable stiffness (VS) composites have been reported to provide significant improvements in performance over constant stiffness designs. The phenomenon of snapping from one stable state to another is of paramount importance for multistable structures to be used in morphing applications. VS laminates allow the designer to tailor structural response according to the requirements of the morphing mechanism. This work presents a parametric study to explore designs by exploiting the tailoring options in VS laminates, with the objective of requiring low snap-through and snap-back voltages but at the same time enabling high out-of-plane displacements with the effective and efficient use of microfiber composites actuators. The fiber orientation of the layers of the VS laminate is assumed to vary linearly from the center to the edge of the plate. Design spaces of different laminates were investigated by varying the three angle parameters defining the VS laminates. Finite element analyses on snap-through and snap-back actions on the bistable nature of VS laminates were performed using the help of macro fiber composite actuators.